Parent-Adolescent Conflict and Its Resolution in Monogamous and Polygamous Bedouin Arab Families in Southern Israel - Salman Elbedour; Joel M. Hektner; Mohammed Morad; Soleman H. Abu-Bader (The Scientific World Journal)
The purpose of this study was twofold: (1) to compare whether children from polygamous family structures significantly differ from children from monogamous family structures with regard to the frequency of parent-child conflict, and (2) whether children from these two structures employ different patterns of family conflict resolution.To address these questions, a random sample of 212 high school students (60.8% monogamous) completed a self-administered survey. The results of MANOVA show no significant differences (p > 0.05) between these two structures with regard to the frequency of parent-child conflict. The results also show similar conflict management styles between these two family structures within each of the following five domains (privacy, school and career, money spending, going out and leisure, and physical appearance).This study is unique in that it is the first empirical research to be conducted in the field of conflict resolution among youth and adolescents in polygamous marital structures and therefore, further investigation is needed to replicate these results utilizing different cross-cultural populations practicing polygamy.